(untitled) (Journal of Mathematical Study, 2015)
We study the growth of solutions of higher order complex differential equations in an angular domain of the unit disc instead of the whole unit disc. Some conditions on coefficient functions, which will guarantee all non-trivial solutions of the higher order differential equations have fast growing, are found in this paper.